Fluctuations of tilapia asymmetry (Oreochromis niloticus) at Marine Mandiri Fisheries Training Center (P2MKP) Water World, Banyuwangi - Darmawan Setia Budi; Lailatul Lutfiyah (Airlangga University, 2017)
Fluctuating asymmetry of the bilateral meristic characteristic is one of the simple methods that can be used to determine the stability of an individual fish development. This study aims to provide quantitative information about the level of asymmetry of Nile tilapia (Oreochromis niloticus) in Dunia Air Independent Training Center Marine and Fisheries, Banyuwangi through bilateral meristic characteristic observation. A total of 120 fish samples (5-7 cm) were measured in this study. Four bilateral meristic characters were calculated i.e. the number of soft pectoral fins, number of soft ventral fins, number of scales on the lateral line up and down. The results show that the highest value of the fluctuating asymmetry of magnitude (FAm) and fluctuating asymmetry of number (FAn) was obtained at the number of scales on the lateral line up those are 2.14 and 0.78, respectively. Meanwhile, the lowest FAm and FAn values obtained from the soft ventral fins which were 1.69 and 0.78, respectively. The sum of the total value of fluctuating asymmetry of each bilateral meristic characteristic was observed. The overall FAm value was 7.83 and the overall FAn value was 2.99.Keywords: fluctuating asymmetry, Nile tilapia, PMKP Dunia Air